Lussazione gleno-omerale: eziopatogenesi, anatomia patologica, classificazioni - Carbone, S.; De Cupis, M. (Lo Scalpello - Journal, 2018)
GLENOHUMERAL INSTABILITY: AETIOPATHOGENESIS, PATHOLOGIC ANATOMY, CLASSIFICATIONS The shoulder is the most frequently dislocated joint in the body owing to its large range of motion and small area of articulation between the humeral and the glenoid surfaces. Traumatic shoulder dislocations, especially those associated with injury to the labroligamentous or bony stabilizers of the joint, lead to further reduction of articular surface contact with resultant glenohumeral instability and recurrent shoulder dislocations. Classification of instability mechanism and direction is important for the choice of the right treatment.